The Use of Mimicry Memorization Method in Learning Speaking Skills at Tarbiyatul Muhibbin Junior High School - Shalihah, Imroatus; Bahruddin, Uril; Fikri, Shofil (JURNAL IJ-ATL, 2024)
Developing speaking skills (maharah kalam) in Arabic requires instructional strategies that emphasize active engagement, structured practice, and contextual relevance. This study investigates the application of the Mimicry Memorization method in enhancing students’ speaking proficiency at Tarbiyatul Muhibbin Junior High School, Banyuwangi. Grounded in the need to address common challenges such as low confidence, poor pronunciation, and limited oral fluency, the research focuses on three key areas: the procedural stages of method implementation, the interactional dynamics during mimicry practice, and the method’s overall contribution to students’ speaking performance. Using a qualitative descriptive approach, data were gathered through classroom observations, interviews with Arabic teachers and students, and document analysis. The findings reveal that structured repetition and guided imitation foster greater student confidence, improve pronunciation, and enhance participation in speaking activities. This study highlights the value of imitation-based methods in Arabic pedagogy and suggests that Mimicry Memorization can serve as an effective strategy for cultivating communicative competence in faith-based language education.